MEIQUE project extension actions to combat the Covid-19 pandemic: “Solidarity Soap” and “More than Soap” Campaigns - Guimarães, Damaris; Fabri, Paulo Henrique; Zago Barbosa, Larissa; de Sousa Anselmo, Adriana (Guará Journal, 2022)
This paper describes the "Solidarity Soap" and "More Than Soap" campaigns, carried out by participants in the extension project "Women Individual Entrepreneurs of Kerosene" (MEIQUE) at the Federal University of Espírito Santo (UFES), Alegre campus. These campaigns aimed to contribute to underserved communities in the municipality of Alegre, Espírito Santo state, in combating the COVID-19 pandemic, through the donation of hygiene kits containing the soap produced by the project, among other items. The campaigns were carried out in April, May, and June 2020. Through social media promotion, donations were collected to assemble hygiene kits that were distributed to the underserved communities of "Morro do Querosene," "Prainha," Vila Alta, "Morro do Sapo," "Morro do Carrapato," "Escadão da Rua 13," "Cantinho do Céu," "Charqueada," and Celina. In total, 200 families in socially vulnerable situations were assisted, with an estimated 700 people benefiting. In addition to the positive social impact, the campaigns raised awareness for the project and resulted in positive consequences for the environment and the personal and professional development of the academic members of the project team.